2009
DOI: 10.1007/s12031-008-9140-0
|View full text |Cite
|
Sign up to set email alerts
|

EGb761 Protects Hydrogen Peroxide-induced Death of Spinal Cord Neurons through Inhibition of Intracellular ROS Production and Modulation of Apoptotic Regulating Genes

Abstract: The present study was conducted to investigate whether Ginkgo biloba extract (EGb) 761 could protect spinal cord neurons from H(2)O(2)-induced toxicity. In primary spinal cord neurons isolated from embryonic day 14 rats, H(2)O(2) administration resulted in a significant decrease in the survival of spinal cord neurons. Terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) and Hoechst 33342 nuclear staining showed that these cells die by apoptosis. Such neuronal death, however, was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
6
20
0
Order By: Relevance
“…The anti-oxidative effect was positively correlated with EGb761 concentration, which is consistent with other reports showing the anti-oxidative property of EGb761 in various cell lines (Jiang et al, 2009;Yeh et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The anti-oxidative effect was positively correlated with EGb761 concentration, which is consistent with other reports showing the anti-oxidative property of EGb761 in various cell lines (Jiang et al, 2009;Yeh et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The current data shows that EGb761 induces cell apoptosis via the caspase-9-mediated apoptotic pathway (Kim et al, 2005;Kotakadi et al, 2008). In our study, we found that low concentrations of EGb761 upregulated the expressions of caspase-9 and caspase-3, which consequently increased BMSC apoptosis, which was consistent with other reports (Jiang et al, 2009;Massieu et al, 2004). In contrast, high concentration of EGb761 inhibited activities of caspase-9 and caspase-3 and eventually significantly reduced BMSC apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, EGb761 has beneficial neuroprotective effects, probably by means of its antioxidant action, which involves the scavenging of free radicals. [10][11][12]17 In this study, we found that the number of apoptotic cells at 3 and 7 DPI in the EGb761-treated group was significantly smaller than that in the control group. HE-staining analysis further revealed that the cavity in the EGb761-treated group was significantly reduced.…”
Section: Discussionmentioning
confidence: 48%
“…Exposure of cells to exogenous H 2 O 2 can induce ROS overproduction (30), leading to peroxidation of membrane lipids and disruption of cellular integrity (31). The present study showed that pretreatment with morroniside reversed H 2 O 2 -induced apoptosis by blocking ROS production.…”
Section: Discussionmentioning
confidence: 99%